2019
DOI: 10.1038/s41467-019-10853-2
|View full text |Cite
|
Sign up to set email alerts
|

Molecular tuning of farnesoid X receptor partial agonism

Abstract: The bile acid-sensing transcription factor farnesoid X receptor (FXR) regulates multiple metabolic processes. Modulation of FXR is desired to overcome several metabolic pathologies but pharmacological administration of full FXR agonists has been plagued by mechanism-based side effects. We have developed a modulator that partially activates FXR in vitro and in mice. Here we report the elucidation of the molecular mechanism that drives partial FXR activation by crystallography- and NMR-based structural biology. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

12
135
0
3

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 77 publications
(150 citation statements)
references
References 44 publications
12
135
0
3
Order By: Relevance
“…In addition, LT-141A reduced CDCA-induced FXR activity in FXR transactivation and Gal4 assays. These results corroborate the partial agonism of LT-141A and are in line with the observation that some partial FXR agonists cause a structural conformation able to bind co-activator and co-repressor peptides [11]. Target gene expression studies revealed that LT-141A does not act as a classical agonist, but as a SBARM.…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…In addition, LT-141A reduced CDCA-induced FXR activity in FXR transactivation and Gal4 assays. These results corroborate the partial agonism of LT-141A and are in line with the observation that some partial FXR agonists cause a structural conformation able to bind co-activator and co-repressor peptides [11]. Target gene expression studies revealed that LT-141A does not act as a classical agonist, but as a SBARM.…”
Section: Discussionsupporting
confidence: 87%
“…In contrast to full FXR agonists, SBARMs are partial agonists. The molecular basis of differential modes of FXR modulation has been investigated recently and shows that the partial agonists DM175 and ivermectin can recruit co-activator and co-repressor peptides at the same time, thereby eliciting a fluid FXR modulation profile [11].…”
Section: Introductionmentioning
confidence: 99%
“…Alternatively, the binding mechanism could involve a mixture of induced fit binding and conformational selection where helix 12 may adopt an active-like conformation prior to the ligand transitioning to the final binding pose in the orthsoteric pocket if the time scale by which helix 12 exchanges out of the pocket is not rate limiting (5). Other NMR studies have similarly found that the orthosteric pocket and helix 12 in other apo-NR LBDs are dynamic on the µs-ms time scale including FXR, PPARα, retinoid X receptor alpha (RXRα), and vitamin D receptor (VDR) (19)(20)(21)27). Thus, the ligand binding mechanism we describe here for PPARγ may occur for other NRs as well, a hypothesis that could be tested by NMR and biophysical studies as demonstrated in this study.…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, ligand binding to nuclear receptors is often described to induce an active conformation (4,(11)(12)(13)(14)(15)(16). However, there is evidence from NMR studies on PPARγ that in the absence of ligand the apo-LBD exchanges between transcriptionally active and transcriptionally inactive/repressive conformations (17) suggesting a role for conformational selection in the ligand binding mechanism of NR agonists, which are thought to stabilize an active conformation from a dynamic ensemble of active and inactive/repressive conformations (15,(18)(19)(20)(21)(22)(23)(24)(25)(26)(27). Taken together, these observations stem from the ability of the ligand-bound NR LBD to exert specific functions such as coactivator interaction and transcription, but not directly on the mechanism of ligand binding to the orthosteric pocket.…”
Section: Introductionmentioning
confidence: 99%
“…FXR has been exploited as a promising target for the treatment of various liver diseases 11 , including liver fibrosis 12 . FXR agonists with diverse chemical structures were developed [13][14][15] , notably obeticholic acid (OCA) 16 , a representative FXR agonist, that was approved for primary biliary cholangitis (PBC) 17,18 . More recently, OCA completed phase III clinical trial for nonalcoholic steatohepatitis (NASH) with fibrosis.…”
mentioning
confidence: 99%